NOX2-Deficient Neutrophils Facilitate Joint Inflammation Through Higher Pro-Inflammatory and Weakened Immune Checkpoint Activities - Liao, Yi-Chu; Wu, Szu-Yu; Huang, Ya-Fang; Lo, Pei-Chi; Chan, Tzu-Yi; Chen, Chih-An; Wu, Chun-Hsin; Hsu, Che-Chia; Yen, Chia-Liang; Chen, Peng-Chieh; Shieh, Chi-Chang (Frontiers in Immunology, 2021)
Immune-mediated arthritis is an important chronic inflammatory disease of joints causing debilitating morbidity in affected patients. The mechanisms underlying immune-mediated arthritis have been intensively investigated, however the cellular and molecular factors contributing to the joint inflammation in different redox conditions have not been clearly elucidated. Previous research showed that phagocyte-produced reactive oxygen species (ROS) plays an anti-inflammatory role in K/BxN serum-induced arthritis and NOX2-deficient mice tend to have more severe arthritis. Although many leukocytes play critical roles in the development of immune-mediated arthritis, the role of neutrophils, which are the main producers of ROS in inflammation, is still controversial. We hence assessed the immunomodulatory function of neutrophils from arthritic joints of NOX2-deficient and wild type mice in this study. We found more neutrophils accumulation in NOX2-deficient inflamed joints. RNA-sequencing and quantitative PCR revealed significantly increased expression of acute inflammation genes including IL1b, Cxcl2, Cxcl3, Cxcl10 and Mmp3 in activated neutrophils from the inflamed joints of NOX2-deficient mice. Moreover, gene set enrichment analysis (GSEA) showed enriched gene signatures in type I and II IFN responses, IL-6-JAK-STAT3 signalling pathway and TNF-a signalling pathway via NF-kB in NOX2-deficient neutrophils. In addition, we found that NOX2-deficient neutrophils expressed lower levels of PD-L1 and were less suppressive than WT neutrophils. Moreover, treatment of PD-L1-Fc decreased cytokine expression and ameliorated the severity of inflammatory arthritis. Our results suggest that NOX2-derived ROS is critical for regulating the function and gene expression in arthritic neutrophils. Both the strong pro-inflammatory and weakened anti-inflammatory functions of neutrophils due to abnormal redox regulation may be targets of treatment for immune-mediated arthritis.